2012
DOI: 10.1159/000342503
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TNF-Alpha Induced Psoriasiform Eruptions with Severe Scalp Involvement and Alopecia: Report of Five Cases and Review of the Literature

Abstract: We describe 5 cases of anti-tumor necrosis factor-alpha (anti-TNF-α) induced psoriasiform eruptions with severe scalp involvement inducing inflammatory alopecia and review the literature on this subject. All our 5 patients were provided topical therapy, with good results in only 1 case. The remaining 4 were provided systemic therapy (methotrexate ± cyclosporine): 3 concomitantly suspended the anti-TNF-α treatment (2 are currently clear/almost clear but 1 has so far only observed mild improvement) and 1 switche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 25 publications
(28 reference statements)
0
51
0
1
Order By: Relevance
“…Scalp psoriasis is usually characterized by discrete psoriatic plaques on the scalp, with or without alopecia, that may itch intensely [3, 4, 9, 10]. In contrast to palmoplantar pustulosis (where rheumatoid arthritis is the most common underlying disease), Crohn’s disease usually underlies the very rare manifestation of tumor necrosis factor alpha antagonist-induced scalp psoriasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scalp psoriasis is usually characterized by discrete psoriatic plaques on the scalp, with or without alopecia, that may itch intensely [3, 4, 9, 10]. In contrast to palmoplantar pustulosis (where rheumatoid arthritis is the most common underlying disease), Crohn’s disease usually underlies the very rare manifestation of tumor necrosis factor alpha antagonist-induced scalp psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to palmoplantar pustulosis (where rheumatoid arthritis is the most common underlying disease), Crohn’s disease usually underlies the very rare manifestation of tumor necrosis factor alpha antagonist-induced scalp psoriasis. A case series and literature review reported 15 such individuals; 80% (12/15) of the patients had a history of Crohn’s disease [10]. …”
Section: Discussionmentioning
confidence: 99%
“…The authors also described lichenoid lesions and pustular folliculitis [18]. Osório et al [19] described 5 cases of anti-TNFα-induced psoriasiform eruptions with severe scalp involvement. Doyle et al [20] described 3 patients who developed psoriasiform lesions on the scalp after the use of anti-TNF drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the scalp, these patients exhibited psoriatic lesions on the trunk, axillae, extremities, genitals, and palms/soles. The onset of hair loss ranged from two [43,44] to 46 [45] months after the TNF-α inhibitor was begun, with an average latency period of 8.6 months. There were 11 females and eight males.…”
Section: Clinical Subtypes Of Alopecia Seen During Treatment With Tnfmentioning
confidence: 99%